2013
DOI: 10.1080/19440049.2012.745097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the main food-borne pathogens in retail food under the national food surveillance system in Japan

Abstract: The National Food Surveillance System in Japan was formed in 1998 to monitor the contamination of retail foods with bacterial pathogens. Approximately 2000-3000 samples were tested annually, and the data from food categories that had more than 400 samples collected during 1998-2008 were analysed. With regard to meat, the frequency of positive samples for Salmonella in chicken for raw consumption and ground chicken was 12.7% and 33.5%, respectively. Moreover, Shiga toxin-producing Escherichia coli (STEC) O157 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
2
23
1
1
Order By: Relevance
“…Guyard‐NicodĂšme et al, reported 64.5% prevalence of C. jejuni in chicken meat. Some research studies reported lower prevalence of C. jejuni in chicken meat than the current study such as; 19.56% (de Moura et al, ), 13.7% (Ma et al, ), and 13.3% (Hara‐Kudo et al, ).…”
Section: Discussioncontrasting
confidence: 50%
“…Guyard‐NicodĂšme et al, reported 64.5% prevalence of C. jejuni in chicken meat. Some research studies reported lower prevalence of C. jejuni in chicken meat than the current study such as; 19.56% (de Moura et al, ), 13.7% (Ma et al, ), and 13.3% (Hara‐Kudo et al, ).…”
Section: Discussioncontrasting
confidence: 50%
“…For example, supermarkets grew from a niche retail market in Latin America, comprising 10 to 20% of the national food retail sales in the 1980s, to the dominant form constituting 50 to 60% of the national sales in 2000 [52]. Supermarkets impose private stringent grades and standards of quality and safety in their procurement of fresh fruits and vegetables from local farmers in developing countries [53,54]. These quality requirements of supermarkets are beneficial for the local consumers, since overall GAP and GHP in local agriculture and food traders is stimulated [55].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the outbreak was so small that it would not have merited any national media coverage and would likely have been confined to the local media in Chiba prefecture, where the most serious case of food poisoning occurred À if it even got that far. Over 1,000 outbreaks and 20,000 cases of food-borne disease have been reported annually in Japan since 1996 (Hara-Kudo et al 2013). Despite this, the relatively small outbreak of food poisoning was national news, and was printed on the front page of both the Asahi and the Yomiuri Shimbun.…”
Section: Risk Harm and Food Contamination In Japanmentioning
confidence: 98%